Evaluation of Mungbean Mutant Lines to Drought Stress and Their Genetic Relationships Using SSR Markers - Y Yuliasti; R Reflinur (PPIKSN-BATAN, 2015)
Development of mungbean cultivarstolerant to drought stress through mutation breeding approach would enable us to anticipate the crop yield-reducing effects of climate changes. The objective of this research was to evaluate the yield performance of mungbean mutant lines that showed tolerance to drought stress, and to analyze their genetic diversity and relationship among mutant lines using SSR markers. The study was conducted during the dry season of 2012 in the Muneng experimental farm, Probolinggo, East Java. The experiment was laid out in a randomized block design with four replications. Five mutant lines and two parental lines as control were tested for evaluation of yield and drought tolerance under twoenvironments of two irrigation systems as treatment. The two environmental conditions consisted of optimal irrigation (at least three times: at planting, flowering and during pod filling) and suboptimal irrigation (two times at planting and flowering). To evaluate genetic variation among selected mutant lines and their discrimination from parental lines in molecular level, a cluster analysis was performed using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) in the NTSYS software. The results showed that three mutant lines, including PsJ30, PsJ31, PsJ32 produced the highest grain yields of 1.17, 1.01, and 1.04 ton/ha, respectively, compared to the other mutant lines and the parents Gelatik (0.85 ton/ha) and Perkutut (0.87 ton/ha) as control check. Of those mutant lines, PSJ31 was the most tolerant to drought with sensitivity index value of 0.47. The PSJ31 has now been officially released as a new variety ( 2013), named as Muri which was identified to have high yield and tolerant to drought. Based on 23 SSR markers used for clustering analysis of those 3 selected mutant lines,9SSR markers (MBSS R033; satt137; MBSSR008; MBSSR203; MBSSR013; MBSSR021; MBSSR016; MBSSR136; and DMBSSR013) were successfully identified the three mungbean mutant lines. Taken together, we have succeeded at develop and evaluate three elite mutant breeding lines which are valuable resources for genetic variation in mungbean. The genetic variation information of mungbean at molecular level potentially provides room for recombinants which are essential for the development of a new superior variety in mungbean improvement.Received: 04 October 2014; Revised: 04 June 2015; Accepted: 16 June 2015